Sheroes, sivas, and other endangered species : black women in higher education - Rasmussen, Natalie D. (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Because of their intersectional identities, African American women in the academy must navigate the many visible and invisible obstacles of racism and sexism. To do so, they might employ several coping mechanisms and strategies to combat deficit-based stereotypes, possibly resulting in the harm of intergenerational trauma and Racial Battle Fatigue. This paper utilizes critical autoethnography and storytelling to interweave my personal narrative that outlines the everyday occurrences of high-performing Black women and the predictable backlash of American white supremacy with supporting literature to illuminate the coping strategies and underpinnings of John Henryism, Armoring, the Superwoman Schema, and Sister Circles.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 9, 2025 Special Issue
Keywords: Black women; Racial battle fatigue; Coping strategies; Critical autoethnography; Women, Black; Racism in higher education; Sexism in higher education; Education, Higher